2021
DOI: 10.1093/ptj/pzab122
|View full text |Cite
|
Sign up to set email alerts
|

Professional and Ethical Issues in United States Acute Care Physical Therapists Treating Patients With COVID-19: Stress, Walls, and Uncertainty

Abstract: Objective: No peer-reviewed research has explored professional and ethical issues encountered by physical therapists in treating patients with COVID-19. The purpose of this study was to explore the experiences of physical therapists regarding the professional and ethical issues they encountered during the COVID-19 pandemic. Methods: The current study used reflexive thematic analysis, a qualitative research design developed by Braun and Clarke, to analyze individual interviews. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 60 publications
2
30
0
2
Order By: Relevance
“…Our results are consistent with previous studies [13,17] showing that once incorporated into ICUs and acute care units, PTs had the feeling of being lost, of not being sufficiently useful or also that they wanted to contribute more. In fact, their training, mainly oriented to rehabilitation and comprehensive recovery of outpatients, could place them in a more vulnerable position in relation to the emotional impact of working in first-line units [14], without having experience and/or training to deal with critical events associated with a situation such as death, disaster situations, and moral dilemmas and conflicts during the COVID-19 pandemic [13,14,17]. Our results also showed that PTs had to self-train to adapt to the demands of the pandemic care.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Our results are consistent with previous studies [13,17] showing that once incorporated into ICUs and acute care units, PTs had the feeling of being lost, of not being sufficiently useful or also that they wanted to contribute more. In fact, their training, mainly oriented to rehabilitation and comprehensive recovery of outpatients, could place them in a more vulnerable position in relation to the emotional impact of working in first-line units [14], without having experience and/or training to deal with critical events associated with a situation such as death, disaster situations, and moral dilemmas and conflicts during the COVID-19 pandemic [13,14,17]. Our results also showed that PTs had to self-train to adapt to the demands of the pandemic care.…”
Section: Resultssupporting
confidence: 92%
“…The presence of these conflicts in the first weeks of the first outbreak in relation to the presence of PTs in units such as the ICU could be justified by the contrast between the sense of duty that led PTs to voluntarily report to acute care [14,17] and the concern in rehabilitation services to find a balance between providing rehabilitation care to as many patients as possible, avoiding the contagion of patients at risk and protecting rehabilitation professionals, as described in countries such as Italy and Spain [6,8,11,32].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations